The Development of the National Football Development Program (NFDP) Coaching Process Model: Emphasis on Small Sided Game (SSG) Approach - Zulakbal Abd Karim; Asraf Razak; Fakrul Hazely Ismail; Abdul Rahman Muhammad; Syed Kamaruzaman Syed Ali; Amin Akbar (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Small-sided games (SSGs) are played on reduced pitch areas, often using modified rules and involving a smaller number of players than traditional football. These games are less structured than traditional fitness training methods but are very popular training drills for players of all ages and levels. At present, there is relatively little information regarding how SSGs can best be used to improve physical capacities and technical or tactical skills in footballers. However, many prescriptive variables controlled by the coach can influence the exercise intensity during SSGs. In the context of soccer instruction, SSGs are frequently employed to give an engaging method of preserving the dynamics of an official game while making particular alterations to concentrate on certain behaviors and movements. Models for coaching provides some insight and guidelines into what coaches do. The purpose of the study is to build a coaching process model based on the "Small Sided Game" approach. The qualitative method was conducted in this study. The researcher used snowball sampling in which 10 sports schools coaches under NFDP program were interviewed. The numbers of participants were determined by saturation of information. The variation in exercise intensity during SSGs can improved with consistent coach encouragement but it is still more variable than traditional generic training methods. SSGs containing fewer players can exceed match intensity and elicit similar intensities to both long- and short-duration high- intensity interval running. This study implied the construction of the football coaching process model that can benefit the national football development at the grassroots level and provide alternative sources of knowledge for teachers or football coaches to coach their football teams.